Elucidation of the role of estradiol and progesterone in regulating reproduction in the edible crab, Oziothelphusa senex senex. Issue 30 (7th March 2016) - Swetha, CH.; Girish, B. P.; Reddy, P. Sreenivasula
Abstract : Vertebrate sex steroids are ubiquitous and important bioactive mediators for many physiological functions. Abstract : Vertebrate sex steroids are ubiquitous and important bioactive mediators for many physiological functions. Progesterone and 17β-estradiol have been detected in few crustaceans and it has been hypothesized that they are involved in the regulation of ovarian maturation. However, in the freshwater crab, Oziothelphusa senex senex, the presence of 17β-estradiol and progesterone, as well as their mechanisms of action on ovarian maturation, have not yet been investigated. In this study, we report the presence of 17β-estradiol and progesterone in the haemolymph of O. senex, and their levels were significantly higher during late vitellogenesis. Moreover, we report that administration of these hormones increased ovarian index, oocyte diameter, and ovarian vitellin levels in the crab. Additionally, the mRNA levels of ecdysteroid receptor and retinoid receptor in the hepatopancreas and ovary, and vitellogenin mRNA levels in the hepatopancreas also increased after administration of progesterone and 17β-estradiol. In silico analysis revealed interaction between vertebrate steroid hormones and the ecdysteroid receptor. The ability of female sex steroids to mimic the effects of ecdysteroids suggests that the vertebrate steroids may represent another group of reproductive endocrines in crustaceans besides peptides (gonad inhibiting/stimulating hormones), terpenoids (methyl farnesoate) and ecdysteroids.